Recent Advances of Disсrete Optimization and Scheduling (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint of this Special Issue of Mathematics presents recent research within the field of discrete optimization and scheduling. The subjects addressed in the ten research papers cover a broad spectrum of optimization algorithms, e.g., papers dealing with nature-inspired algorithms, routing problems in plane graphs, the scheduling of surgeries in operation rooms, or single machine scheduling problems.